Kerja Sama Pemerintah Bersama Masyarakat dalam Menanggulangi Korupsi Dana Desa (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This kind of research can reveal a purpose, namely to be able to carry out an analysis of the important role of the government together with the community in realizing policies to combat corruption of village funds. It is necessary to understand that village funds have been made one of the government's priority programs in order to increase the level of prosperity of rural communities and village development through the Village Law. Therefore, the purpose of this study is to identify policy solutions provided by the government and the community to prevent corruption of village funds. This study utilizes a literature study method through a qualitative approach that can be used to assess the role of the government and the community in implementing policies to combat corruption of village funds as an effort to uphold the integrity of the village administration system. Meanwhile, the research data sources obtained came from secondary data, which included the collection of scientific journals in the last five years, reading books in the last ten years, reports in the mass media, and government regulations. The findings of this study describe that the Corruption Eradication Commission (KPK) has identified several loopholes that are often exploited by village officials in misappropriating Village Funds. Then there were 98 cases of corruption that caused the state to lose up to Rp. 37.2 billion. This creates an urgency for the government and the community to play a role in creating village regulations that are capable of overcoming corruption of village funds.